Outcome of Surgery in a Patient with Blindness and Inter- Hemispheric Cyst: A Case Report - Kaisar Haroon; Taher, T; Ahmad, MU; Md Motasimul Hasan; Md Shafiul Alam; Hossain, SK Sader (Bangladesh Journal of Neurosurgery, 2024)
Interhemispheric cysts are rare congenital condition which is also associated with corpus callosum agenesis. Most patients present at neonatal age or early childhood with some neurological deficiency. Some patients may present at older age. Here we present a patient with acute blindness of the right eye and dimness of vision of the left eye. He had no mental retardation or other neurological deficit. His fundus showed bilateral papilloedema. His MRI showed an interhemispheric cyst with agenesis of the corpus callosum. He was urgently operated in this hospital. The cyst was approached through interhemispheric fissure. It was excised and communicated with the third ventricle. His post-operative period was uneventful. Immediately after surgery he had improvement of his vision over a period of two week. He could return to normal life following discharge. Therefore, prompt surgical intervention is important for saving vision of these patients. Bang. J Neurosurgery 2024; 13(2): 165-169